Increased Graduation Rates in Students Who Take One or More Experiential Learning Classes during Their Undergraduate Program of Study: The EXL Scholars Program at Middle Tennessee State University provides hands-on experiences, service learning, networking with professionals, and career exploration through real-world activities. The program is now institutionalized, and students who participate graduate at a significantly higher rate. - Rost, Jim; Swayze, Anita Carol; Janet McCormick, (Experiential Learning and Teaching in Higher Education, 2023)
A large American university in the southeastern United States has infused experiential learning into academic courses to create a national model that is both sustainable and replicable. The EXL Scholars Program has consistently shown growth and significant positive outcomes by providing students with opportunities for hands-on experiences in their fields of study, service learning opportunities, valuable networking with professionals, and an opportunity to explore career paths through real-world activities. Student learning assessments provide evidence that the EXL Scholars Program has a positive benefit for students and does enhance students’ learning experiences as stated in the program’s motto, EXL: Experience the Advantage. This article will explore how the program has been institutionalized and how students who participate in the Experiential Learning Scholars Program graduate at a significantly higher rate than those students who do not.